Implementasi Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Jamaluddin, Nur Alam; Hasyim, Mutahharah; Addas, Arniati (Universitas Negeri Makassar, 2024)
Abstract. This research aims to determine the improvement in students' physics learning outcomes by using the problem based learning model. This research was classroom action research with research subjects in class XI MIPA 2 as many as 30 students. This classroom action research was conducted at SMAN 6 Enrekang. This research was carried out using two cycles of action or cycles, where each cycle consists of four stages, namely: 1) Design (Planning), 2) Implementation of Activities and Observations (Acting), 3) Observation (Observing), and 4) Reflection ( Reflecting). Based on the research that has been conducted, it was found that the average physics learning outcome of students in cycle I was 70.90 and the average physics learning outcome of students in cycle II was 75.90. Based on the research and discussions that have been carried out, it can be concluded that the application of the problem based learning model can improve students' physics learning outcomes. Keywords: Problem Based Learning Model, Learning Outcomes